Prescribing playing intensity in small-sided games using rating of perceived effort among youth soccer players: a randomized crossover trial - Kobi, O., Ben-Ari, A., Dello Iacono, A., Silverman, Y., Obolski, U., & Halperin, I. (Science and Medicine in Football, 2026)
In this study, we examined whether the 0-10 rating of perceived effort (RPE) scale can serve as a method for prescribing playing intensity in small-sided games (SSGs). We conducted a randomized crossover trial involving 25 young male football players (age range 16-18 years). Participants completed a familiarization and three experimental sessions where game intensity was regulated using prescribed intensities equal to RPE of 6, 8, or 10. Each session involved six teams of three players playing in three SSGs, with 4 min of rest, in a playing area of 133 square meters per player. Outcomes included total distance, high-speed running distance (HSRD), intense acceleration and deceleration (IAD) counts, and average heart rate (HR). We fitted mixed models and estimated 95% confidence intervals (CIs) to analyze the results. The CIs for all locomotive outcomes indicated an increase at RPE-8 and RPE-10 compared to RPE-6. Notably, the effects on HSRD and IAD were substantial, with differences between RPE-10 and 8 to RPE-6 ranging from 28% to 97%. Conversely, differences in the total distance the players covered per game between RPE-10 and 8 to 6 were minor (~5%). We could not identify clear differences between RPE-10 and 8 in the locomotive outcomes (differences range 0%-9.6%, CIs containing zero) nor in HR across all RPE conditions (differences range 1-3.5 bpm, CIs containing zero). We conclude that RPE can serve as a practical tool to prescribe medium or high intensity during SSGs, although its ability to differentiate between higher intensity levels or influence heart rate is limited.